Influence of the postpolymerization type and time on the flexural strength and dimensional stability of 3D printed interim resins - Silva, Nathalia R.; Moreira, Fernanda G. de G.; Cabral, Ana B. de C.; Bottino, Marco A. [UNESP]; Marinho, Renata M. de M. [UNESP]; Souza, Rodrigo O.A. (Elsevier, 2023)
Statement of problem: The mechanical strength of 3-dimensionally (3D) printed interim resins is unclear but influenced by printing parameters. Evidence regarding standardization of the postpolymerization type and time for 3D printed interim resins is sparse. Purpose: The purpose of this in vitro study was to evaluate the influence of postpolymerization type and time on flexural strength and dimensional stability of 3D printed resins for interim restorations. Material and methods: A total of 288 bars were 3D printed (Form 2; Formlabs, stereolithography—SLA, 50 µm, 30 degrees), (25×2×2 mm; International Organization for Standardization—ISO 4049:2019) abraded and randomly divided into 9 groups (n=30) according to postpolymerization (Ultraviolet device—UV; Microwave with water—MWA; Microwave without water—MW) and time (15, 20, and 30 minutes for UV; and 5, 8, and 10 minutes for MW and MWA). Each bar was then measured with digital calipers at 11 points for length, thickness, and width before and after postpolymerization to analyze dimensional stability. The flexural strength was then measured (σ; 980.6 N, 1 mm/minute) and the fractured surfaces were analyzed with scanning electron microscopy. The σ (MPa) data were evaluated by using a 2-way analysis of variance (ANOVA) and the Tukey honestly significant difference (HSD) pairwise comparisons test (α=.05). Dimensional stability data (mm) were analyzed by using the Kruskal-Wallis test and Dwass-Steel-Critchlow-Fligner multiple comparisons. The Weibull analysis was performed with σ data. Results: The 2-way ANOVA revealed that all factors and their interaction were significant for σ (P<.001). The UV groups presented the highest σ values, being statistically higher than all MW and MWA groups. The Weibull analysis revealed that postpolymerization UV groups found the highest values regarding the characteristic strength, although the MW 8-minute group (13.71) found the highest value for the Weibull modulus. Furthermore, the Kruskal-Wallis test revealed that only the postpolymerization factor was significant for dimensional stability (P<.001). The postpolymerization microwave groups found greater expansion variations at all times, with the MW 8-minute group (0.78 ±0.54) presenting the greatest variation in dimensional stability. Conclusions: UV was determined to be the most suitable type of postpolymerization for interim printed resin among the postpolymerization methods, regardless of the application time. The postpolymerization MW groups found greater variations in dimensional stability.